Ewolucja rachunku kosztów działań w warunkach globalnej gospodarki - Kozłowska, Katarzyna; Wroński, Paweł (The evolution of Activity-Based Costing methodology in terms of global economy, 2008)
Activity-Based Costing was believed to be an excellent alternative to the traditional way of accounting. Nevertheless, ABC came to be viewed as too time-consuming, laborious to be worth implementing and costly to maintain and update. The developed concept overcoming these difficulties is called Time-Driven ABC. The new approach is perceived as an easier, faster and less expensive methodology. It generates comprehensive analysis of profitability across the enterprise. Although the-new concept has its disadvantages, it surely gives managers another tool for oversight of corporate; performance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 231-238